Zika and Rio Olympic Games. Issue 4 (July 2016) - Shadgan, Babak; Pakravan, Amir; Zaeimkohan, Hamid; Shahpar, Farhad Moradi; Khodaee, Morteza
Abstract : Zika virus (ZIKV) is an arthropod-borne virus that is mainly transmitted via a bite from a female mosquito of the Aedes species. However, ZIKV can be transmitted sexually or via blood. Due to the recent ZIKV outbreak in South and Central America, many national and international organizations are concerned about the safety of athletes, coaches, staff, and spectators during the Olympic and Paralympic Games. Infected individuals are generally asymptomatic or have mild symptoms. However, ZIKV infection can potentially cause serious complications such as Guillain-Barre syndrome and congenital defects. Preferred diagnosis is based on real-time reverse-transcription polymerase chain reaction from blood and urine. Currently, there is no treatment or immunization available for ZIKV infection, and disease control is limited to preventing mosquito bites.